Substituting corn grain for passion fruit peels in feed for confined sheep - Pazdiora, Raul Dirceu; Pazdiora, Bruna Rafaela Caetano Nunes; Queiroz, Edicarlos Oliveira; Mendonça, Talita Oliveira [UNESP]; Cândido, Fernanda Dos Santos; Anjos, Mariana Moreira Dos; Matos, Islan Junior Rodrigues De; Andrelino, André Luiz Silva (UFBA - Universidade Federal da Bahia, 2021)
The aim of this study was to evaluate diets substituting corn grain with passion fruit peels on the consumption, ingestive behavior, digestibility of diets and sheep performance. A total of 20 sheep were used, confined in individual pens, fed twice a day, with diets which included passion fruit peels in the proportions of 0; 25; 50; 75 and 100% replacing corn grain. The corn grain represented 70% of the dry matter of the diet and the passion fruit peels were supplied in dehydrated form. The experimental design was completely randomized with five treatments and four replicates. The data were submitted to analysis of variance and regression analysis at the significance level of 5%. There was a linear increase in dry matter consumption with an increase of 3.89 g for each inclusion level of passion fruit peel. The apparent digestibility of dry matter decreased and neutral detergent fiber increased linearly with the substitution of corn grain with passion fruit peels. The feeding, rumination, leisure and water intake times presented averages of 3.74; 2.92; 16.92 and 0.42 hours, and were not influenced by the diets (P>0.05). The average daily weight gain was similar for the animals in the different diets and consequently the final weight presented average values of 0.226 kg day-1 and 32.1 kg, respectively. The inclusion of passion fruit peels in the sheep diet is an interesting alternative because even with the reduced dry matter digestibility, it increased the consumption and promoted similar weight gains.

Objetivou-se avaliar dietas com substituição do grão de milho pela casca de maracujá sobre o consumo, comportamento ingestivo, digestibilidade das dietas e desempenho de ovinos. Foram utilizados 20 ovinos, confinados em baias individuais, alimentados duas vezes ao dia, com dietas que receberam a inclusão da casca de maracujá nas proporções de 0; 25; 50; 75 e 100% em substituição ao grão de milho. O grão de milho representou 70% da matéria seca da dieta e a casca de maracujá foi fornecida na forma desidratada. O delineamento experimental foi inteiramente casualizado, com cinco tratamentos e quatro repetições. Os dados foram submetidos à análise de variância e análise de regressão, ao nível de 5%. Observou-se um aumento linear do consumo de matéria seca, com acréscimo de 3,89 g para cada nível de inclusão de casca de maracujá. A digestibilidade aparente da matéria seca reduziu e a fibra detergente neutro aumentou linearmente com a substituição ao grão de milho pela casca de maracujá. O tempo de alimentação, ruminação, ócio e ingestão de água, com médias de 3,74; 2,92; 16,92 e 0,42 horas, não foram influenciados pelas dietas (P>0,05). O ganho de peso médio diário foi semelhante para os animais nas diferentes dietas e por consequência o peso final, apresentando valores médios de 0,226 kg dia-1 e 32,1 kg, respectivamente. A inclusão de casca de maracujá na dieta de ovinos é uma alternativa interessante, pois mesmo com a redução da digestibilidade da matéria seca, aumentou o consumo e promoveu semelhante ganho de peso.
Substituição do grão de milho pela casca de maracujá na alimentação de ovinos confinados
Keywords: Non-conventional foods; Productive performance; Ovinoculture; Intensive system; Ruminant; Alimentos não convencionais; Desempenho produtivo; Ovinocultura; Sistema intensivo; Ruminante